The effect of feeding different glycerol sources on the performance of lactating sows - Vida, Orsolya; Egri, Borisz; Tóth, Tamás (Acta Agraria Debreceniensis, 2018)
Glycerol is a by-product of the biodiesel industry and it might be a good alternative to moderate the energy deficiency of sows during the lactation period. Preliminary experiments were carried out to test the effect of a powder, solid based “food grade” glycerol source with 72.9% glycerol content (Trial 1) and a liquid “feed grade” glycerol source with 86% glycerol content (Trial 2) on the performance of lactating sows and their litters. Trial 1 was conducted with 5 Hungarian Large White×Hungarian Landrace sows/treatment (313±24.9 kg) and Trial 2 with 12–12 DanAvl (323±17.0 kg) sows and their litters/treatment. Neither the solid, powder based glycerol (Trial 1), nor the liquid glycerol source (Trial 2) had significant effect on the feed intake, reduction in live weight and back-fat thickness, and weaning-tooestrus interval (p>0.05) of lactating sows. In Trial 2, on the 14th, 21st and 27th days of lactation the milk samples were collected and it was found that 50 kg/t glycerol decreased the protein content of milk samples (p0.05). In Trial 2, no significant difference was found between control and experimental sow groups in triglyceride concentration of blood samples and in the activity of liver enzymes (ALT, AST, GGT; p>0.05), but the concentration of plasma glucose and cholesterol increased tendentiously (p